Estudo da cinética da translocação do fator de crescimento epidermal (EGF) para o núcleo e da sua localização subnuclear em células-tronco mesenquimais e em células tumorais da linhagem SK-HEP-1 - Camila Cristina Fraga Faraco (2017)
By interacting with its receptor (EGFR), epidermal growth factor (EGF) activates cell signaling pathways involving proliferation, migration, differentiation and tumourigenesis. This receptor can be found in cell nucleus, where it has functions in DNA synthesis and repair, transcriptional regulation and oncological processes. Nuclear EGFR has been associated with a worse prognosis and with treatment resistance in cancer patients. Models that characterize the translocation of ligandstimulated receptor to the nucleus have been established. However, the kinetics of this translocation and its comparison between different cell types is not well studied. Furthermore, little is known about the nuclear components involved in this traffic. Thus, we evaluated the EGF translocation kinetics to the nucleus in human adipose tissuederived mesenchymal stem cells (hASC) and in SK-HEP-1 tumor cells, which have mesenchymal characteristics. Cells were stimulated by EGF conjugated to Alexa Fluor® 488 for 5, 10, 20 and 40 minutes and they were analyzed by superresolution microscopy. Images of serial optical sections were acquired to quantify the number and volume of EGF clusters in the nucleus at each stimulation time. We observed that the kinetics of EGF translocation differs between the two cell types, since hASC appear to achieve translocation equilibrium within 10 minutes of stimulation while in SK-HEP-1 cells the translocation continues to occur at later times. We verified that EGF clusters appear to assemble in the cell nucleus at later times, which suggests specific subnuclear localizations for this receptor. When we analyzed the presence of EGF in two nuclear organelles, the nucleoplasmic reticulum and the nucleolus, we observed that some clusters are located in both. This suggests that the nucleplasmic reticulum may be involved in the mechanism of EGFR translocation to the nucleus and that this receptor performs specific functions in the nucleolus. Some clusters were diffusely scattered in the nucleoplasm, suggesting that EGFR may also be in other nuclear organelles. These results indicate that the study of EGF translocation and its subnuclear localization in different cell types can contribute to unravel mechanisms related to EGFR functions in the cell nucleus.